On drug resistance and metronomic chemotherapy: A mathematical modeling and optimal control approach - Urszula Ledzewicz; Shuo Wang; Heinz Schättler; Nicolas André; Marie Amélie Heng; Eddy Pasquier (Mathematical Biosciences and Engineering)
Effects that tumor heterogeneity and drug resistance have on the structure of chemotherapy protocols are discussed from a mathematical modeling and optimal control point of view. In the case when two compartments consisting of sensitive and resistant cells are considered, optimal protocols consist of full dose chemotherapy as long as the relative proportion of sensitive cells is high. When resistant cells become more dominant, optimal controls switch to lower dose regimens defined by so-called singular controls. The role that singular controls play in the structure of optimal therapy protocols for cell populations with a large number of traits is explored in mathematical models.